A matter of design in the South East Asian wooden furniture industry - Ratnasingam, J. (Springer Verlag, 2003)
South East Asia has emerged as a large furniture-exporting region in the world. Wood is the predominant furniture raw material used in the region, although other raw materials are also available. As a large contract-manufacturing base, the South East Asian furniture industry has not developed its original design and innovative capabilities, which has hampered its effort to produce greater value added furniture. New industrial policies and education schemes to diversify the furniture making raw materials are required to enhance the innovative capacity within the industry, if the regional furniture industry is to successfully shift to higher value added furniture manufacturing.